2015
DOI: 10.1002/ejoc.201500184
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diazirine‐Based Photoreactive Saccharin Derivatives for the Photoaffinity Labeling of Gustatory Receptors

Abstract: Saccharin is one of the most common artificial sweeteners that has a bitter taste at high concentrations. Currently, there are no detailed functional analyses of these gustatory receptors. Therefore, we designed and synthesized photoreactive saccharin derivatives that contain a (trifluoromethyl) diazirinyl moiety at the 5- or 6-position for use as functional analysis tools for photoaffinity labeling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…[69,70] Am ajor advance in the use of aryl diazirines for PALw as achieved in 1980 when Brunner et al reported the efficient synthesis and photochemical properties of para-substituted trifluoromethyl phenyld iazirines-reagents whichh ave become the mainstay of most modern applicationso fP AL. [23] Recent examples which highlight the synthetic versatility of incorporating trifluoromethyl phenyld iazirines into complex structures include ( Figure 4): the synthesis of ap hotoactivatable version of the potent topoisomerase II inhibitor etoposide (compound 8); [71] ap hotoactivatable derivative of the artificial sweetener saccharin for potential use in elucidating the mechanismst hat underpin our sense of taste (compound 9); [72] and ap hotoactivatable version of the heat-shock protein 90 (HSP90) inhibitor novobiocin (compound 10)f or elucidating the mechanism of drug binding to the C-terminal protein domain. [73]…”
Section: Aryl Diazirinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[69,70] Am ajor advance in the use of aryl diazirines for PALw as achieved in 1980 when Brunner et al reported the efficient synthesis and photochemical properties of para-substituted trifluoromethyl phenyld iazirines-reagents whichh ave become the mainstay of most modern applicationso fP AL. [23] Recent examples which highlight the synthetic versatility of incorporating trifluoromethyl phenyld iazirines into complex structures include ( Figure 4): the synthesis of ap hotoactivatable version of the potent topoisomerase II inhibitor etoposide (compound 8); [71] ap hotoactivatable derivative of the artificial sweetener saccharin for potential use in elucidating the mechanismst hat underpin our sense of taste (compound 9); [72] and ap hotoactivatable version of the heat-shock protein 90 (HSP90) inhibitor novobiocin (compound 10)f or elucidating the mechanism of drug binding to the C-terminal protein domain. [73]…”
Section: Aryl Diazirinesmentioning
confidence: 99%
“…Synthesis of aliphatic diazirines is straightforward and can be readily accomplished in high yields by using the improved methods reported by Wang et al [78] As mentioneda bove,t he propensity of aliphatic diazirines to undergo rapid b-H atom transfer leading to an alkene product, as well as photoinitiated rearrangement to give the diazo isomer which undergoes nucleophilic reactions with the solvent, are major limitations of Structures of recent photoactiveprobesused to study the mechanismsofa ction for different anti-cancerd rugs and artificial protein substrates. [71][72][73] Chem. Eur.J.…”
Section: Aliphatic Diazirinesmentioning
confidence: 99%
“…Photoaffinity labeling [ 1 , 2 , 3 , 4 , 5 ] has emerged as a powerful methodology in the field of biology due to its availability for elucidating the interactions between bioactive molecules and proteins. Various photophores—including phenyl azides, benzophenones, and diazirines—are commonly employed in this field [ 6 , 7 , 8 , 9 , 10 , 11 ]. Under UV irradiation, photophores are converted into highly reactive intermediates which can form covalent bonds between ligands and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…21,23 Lastly, diaziridine 1.4 can be oxidised to diazirine 1.5 under a suite of conditions, including iodine and triethylamine. 24 These TPD routes are well established and can produce near quantitative yields.…”
Section: Tpd Synthesismentioning
confidence: 99%
“…These TPD routes are well established and can produce near quantitative yields. 24 It should be noted that reaction between the trifluoromethyl ketone, ammonia and HOSA, as used for aliphatic diaziridines, is reported to form a stable hemiaminal adduct which does not readily undergo dehydration. 228 Scheme 7.3.…”
Section: Photoaffinity Labellingmentioning
confidence: 99%